The two-fluid dynamics and energetics of the asymmetric magnetic reconnection in laboratory and space plasmas. Issue 1 (December 2018) - Yamada, M.; Chen, L.-J.; Yoo, J.; Wang, S.; Fox, W.; Jara-Almonte, J.; Ji, H.; Daughton, W.; Le, A.; Burch, J.; Giles, B.; Hesse, M.; et al.
Abstract Magnetic reconnection is a fundamental process in magnetized plasma where magnetic energy is converted to plasma energy. Despite huge differences in the physical size of the reconnection layer, remarkably similar characteristics are observed in both laboratory and magnetosphere plasmas. Here we present the comparative study of the dynamics and physical mechanisms governing the energy conversion in the laboratory and space plasma in the context of two-fluid physics, aided by numerical simulations. In strongly asymmetric reconnection layers with negligible guide field, the energy deposition to electrons is found to primarily occur in the electron diffusion region where electrons are demagnetized and diffuse. A large potential well is observed within the reconnection plane and ions are accelerated by the electric field toward the exhaust region. The present comparative study identifies the robust two-fluid mechanism operating in systems over six orders of magnitude in spatial scales and over a wide range of collisionality. Magnetic energy in the plasma is transferred into particle energy by magnetic reconnection. Here the authors show the two-fluid dynamics of asymmetric magnetic reconnection in two different spatial scales of plasma, namely laboratory and astrophysical plasma.